Wireless hacking projects for Wi-Fi enthusiasts - Barken, Lee.; Bermel, Eric. (Rockland, MA : Syngress ; [Sebastopol, CA] : Distributed by O'Reilly Media in the United States and Canada, 2004)
Sales of wireless LANs to home users and small businesses will soar this year, with products using IEEE 802.11 (Wi-Fi) technology leading the way, according to a report by Cahners research. Worldwide, consumers will buy 7.3 million wireless LAN nodes--which include client and network hub devices--up from about 4 million last year. This third book in the "HACKING" series from Syngress is written by the SoCalFreeNet Wireless Users Group and will cover 802.11a/b/g (Wi-Fi) projects teaching these millions of Wi-Fi users how to "mod" and "hack" Wi-Fi access points, network cards, and antennas to run various Linux distributions and create robust Wi-Fi networks. Cahners predicts that wireless LANs next year will gain on Ethernet as the most popular home network technology. Consumers will hook up 10.9 million Ethernet nodes and 7.3 million wireless out of a total of 14.4 million home LAN nodes shipped. This book will show Wi-Fi enthusiasts and consumers of Wi-Fi LANs who want to modify their Wi-Fi hardware how to build and deploy homebrew Wi-Fi networks, both large and small. * Wireless LANs next year will gain on Ethernet as the most popular home network technology. Consumers will hook up 10.9 million Ethernet nodes and 7.3 million wireless clients out of a total of 14.4 million home LAN nodes shipped. * This book will use a series of detailed, inter-related projects to teach readers how to modify their Wi-Fi hardware to increase power and performance to match that of far more expensive enterprise networking products. Also features hacks to allow mobile laptop users to actively seek wireless connections everywhere they go! * The authors are all members of the San Diego Wireless Users Group, which is famous for building some of the most innovative and powerful "home brew" Wi-Fi networks in the world.
Cover; Contents; Foreword; Introduction; Introduction to Wireless Hacking; A Brief Overview of the Wireless World; SoCalFreeNet.org: Building Large Scale Community Wireless Networks; Securing Our Wireless Community; Hacking Projects; Wireless Access Points; Wireless Client Access Devices; Wireless Operating Systems; Monitoring Your Network; Low-Cost Commercial Options; Mesh Networking; Antennas and Outdoor Enclosure Projects; Antennas; Building Outdoor Enclosures and Antenna Masts; Solar-Powered Access Points and Repeaters; Wireless 802.11 Hacks; Index; Related Titles
Includes index.
Includes bibliographical references and index.
Keywords: Wireless LANs -- Handbooks, manuals, etc; Wireless LANs -- Security measures -- Handbooks, manuals, etc; Electronic villages (Computer networks) -- Handbooks, manuals, etc; IEEE 802.11 (Standard); Electronic books